Mechanisms of Vascular Damage in Gout and Oxalosis: Crystal Induced, Granulocyte Mediated, Endothelial Injury - Boogaerts, M A; Hammerschmidt, D E; Roelant, C; Verwilghen, R L; Jacob, H S (Thrombosis and Haemostasis, 1983)
Immune triggered granulocyte (PMN)-endothelial interactions have been implicated in the pathogenesis of vascular diseases. While hyperuricemia and gout are associated with an increased risk of atherogenesis, we studied the modulation by mono- sodiumurate (MSU) crystals of PMN-endothelial interactions in vitro. The relationship between calciumoxalate (COX) crystals - implicated in the vasculitis of primary oxalosis - and immunologically mediated endothelial injury was also explored.Both MSU- and COX-crystals activate complement (C), as illustrated by the finding of strong PMN aggregating activity and large amounts of C3a and C5a-anaphylatoxin in MSU- and COX- crystal incubated sera.MSU- and COX-crystal treated sera stimulate PMN to adhere to and induce significant 51Cr-release from endothelial cells in vitro. Platelets significantly increase crystal-triggered PMN endothelial cell adherence and 51Cr-release. This platelet augmenting effect depends on the release of platelet constituents (e. g. serotonin).Microcrystalline material present in vessel walls, thus may cause C-activation and may trigger PMN and platelets to damage endothelium in vitro and in vivo. These findings may have relevance to the understanding of the accelerated atherogenesis of hyperuricemia and the fulminant vasculitis of oxalosis or ethylene glycol poisoning.
Keywords: Hyperuricemia; Gout; Oxalosis; Endothelium; Granulocytes; Immune damage; Complement